The Relationship of Nurse Therapeutic Communication with Anxiety Level in Preoperative Patients at Santa Elisabeth Hospital Medan - Helinida Saragih; Imelda Derang; Friska Sembiring; Resdiadur Bintang Sitohang (Jurnal Ventilator, 2025)
Anxiety is an emotional response to uncertainty or threats that cause feelings of anxiety, worry, excessive tension, which are continuous and can interfere with the patient's process of action and healing, therefore it is necessary to have good and correct therapeutic communication, to build a relationship of mutual trust, empathy, support and help the patient in problem solving. This study aims to identify the Relationship between Nurse Therapeutic Communication and Anxiety Level in Preoperative Patients at Santa Elisabeth Hospital Medan in 2024. The research design uses correlational with a cross sectional approach, purposive sampling technique with a sample of 64 respondents. The instruments used were the nurse therapeutic communication questionnaire and the anxiety questionnaire. The results of the study showed that the majority of therapeutic communication among nurses in the inpatient room of Santa Elisabeth Hospital Medan was in the good category as many as 34 respondents (53.1%), and the level of anxiety of preoperative patients was majority in the medium category as many as 30 respondents (46.9%). The spearman rank statistical test on SPSS obtained a P-Value = 0.000 which means that there is a relationship between the therapeutic communication of nurses and the level of patient anxiety at Santa Elisabeth Hospital Medan. It is expected that the nurses in Pauline's room will further improve therapeutic communication to pre-operative patients.